The Effect of BI Rateâs Decrease Toward The Market Reaction in Indonesia Stock Exchange (IDX) - Sumantyo, Riwi; Anggraeni, Devi (Universitas Muhammdaiyah Surakarta, 2016)
This research aims to analyze the market reactionÂ that can be seen from the abnormal return and trading volume of activity against BI rateâs decrease announcement which is the lowest point in 2011.Â Research methods using paired samples t-test. Data used in this research include the date of announcement of the BI rate which is used as the event date (t0), daily closing share price of companies in a period of observation, LQ-45 index daily, the number of shares traded or daily volume, and the number of shares in circulation or listed share. This research uses 39 companiesÂ listedÂ in the LQ 45 Index listed in BEI as samples. Result of this research is the absence of differences of Abnormal Return and Trading Volume of Activity before and after the announcement. The possibility of this situation was caused by the negative sentiment arising due to the debt crisis in Europe that there is never a solution so it affects the psychology of investors un decision-making.